Spatial variations of trace elements contents in macrophytes within Belarusian lakes - Zhukovskaya, Natalia V.; Kavalchyk, Nadzeya V.; Vlasov, Boris P.; Molenda, Tadeusz (Journal of the Belarusian State University. Geography and Geology, 2019)
The spatial variation of trace elements contents of heavy metals (Ti, V, Cr, Mn, Ni, Cu, Pb) in higher aquatic plants of Belarusian lakes has been analyzed according to monitoring data. Natural variability limits of metals contents in aquatic plants of lakes within principal rivers basins of Belarus have been determined. The data on trace elements contents in macrophytes of Belarus are comparable with the data obtained in Poland and other neighbouring countries. Aquatic plants in lakes are characterized by selective metals accumulation, which is different for ecological groups of submersed, emergent and macrophytes with floating leaves. Statistically significant differences between river basins in the contents of Mn, Cu and Pb have been established in the submersed macrophytes. For all ecological groups, the highest concentrations of Mn in lakes macrophytes tissues are observed in the basins of the Dniapro, Prypiać, Zachodni Buh, and the lowest – the Biarezina. The lakes of the Zachodni Buh and Dniapro basins are distinguished by lower Pb concentrations in aquatic plants. Significant differences in the content of Mn and Cu in the plant tissues within different trophicity lakes have been established. The lowest concentrations of Mn are observed in mesotrophic lakes with signs of oligotrophy. Group analysis of lakes based on the content of Mn, Cu, Pb in macrophyte tissues and spatial constraints has been performed. Among the allocated groups are the lakes of the Braslav district characterized by elevated content of Mn and Cu; lakes of the Vilija basin, distinguished by the lowest average levels of Cu and Pb; lakes of the northern part of Belarus, notable for increased contents of Cu and Pb.
Keywords: trace elements; higher aquatic plants; ecological groups; spatial variability; monitoring; lakes trophic level